2012
DOI: 10.1186/1755-8166-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Is routine karyotyping required in prenatal samples with a molecular or metabolic referral?

Abstract: As a routine, karyotyping of invasive prenatal samples is performed as an adjunct to referrals for DNA mutation detection and metabolic testing. We performed a retrospective study on 500 samples to assess the diagnostic value of this procedure. These samples included 454 (90.8%) chorionic villus (CV) and 46 (9.2%) amniocenteses specimens. For CV samples karyotyping was based on analyses of both short-term culture (STC) and long-term culture (LTC) cells. Overall, 19 (3.8%) abnormal karyotypes were denoted: four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…1:200 general population risk for a submicroscopic clinically significant chromosomal abnormality. Once the miscarriage risk of the invasive sampling procedure has been accepted, a SNP array (with minimum 0.5‐Mb resolution) should be considered, although it has been suggested that standalone RAD would be sufficient for such an indication.…”
Section: Introductionmentioning
confidence: 99%
“…1:200 general population risk for a submicroscopic clinically significant chromosomal abnormality. Once the miscarriage risk of the invasive sampling procedure has been accepted, a SNP array (with minimum 0.5‐Mb resolution) should be considered, although it has been suggested that standalone RAD would be sufficient for such an indication.…”
Section: Introductionmentioning
confidence: 99%
“…A few years ago, several laboratories introduced rapid aneuploidy testing for detection of trisomy 13, 18, and 21, triploidy, and aneuploidy of sex chromosomes as a standalone test for molecular and metabolic referrals. 1,2 Recent advances in microarray testing in pregnancies without ultrasound anomalies led to new insights into the prevalence of submicroscopic chromosome aberrations in such fetuses. Some large-scale studies showed a significant percentage (0.5%) of pathogenic submicroscopic findings in pregnancies tested due to advanced maternal age or abnormal first-trimester screening.…”
mentioning
confidence: 99%
“…These cells had undergone a double enzymatic treatment (trypsin then collagenase) identical to that used before culture of the placental villi. Enzymatic dissociation with trypsin followed by collagenase has been shown to isolate cell populations consisting predominantly of cells from the mesenchymal core [23,24,25,26,27]. In the uncultured cells, the distribution of fluorescence intensity was normal (fig.…”
Section: Discussionmentioning
confidence: 99%
“…In order to isolate a large majority of placental mesenchymal core cells, placental villi underwent a double enzymatic treatment [23,25]. First, a trypsin-EDTA solution (Sigma-Aldrich, St. Louis, Mo., USA) was applied for 20-30 min; second, a collagenase solution (Sigma-Aldrich) was applied for 30-60 min, depending on the quantity of villi.…”
Section: Methodsmentioning
confidence: 99%